Small-molecule MDM2/X inhibitors and PROTAC degraders for cancer therapy: advances and perspectives - Yuan Fang; Guochao Liao; Bin Yu (Elsevier, 2020)
Blocking the MDM2/X-P53 protein-protein interaction has been widely recognized as an attractive therapeutic strategy for the treatment of cancers. Numerous small-molecule MDM2 inhibitors have been reported since the release of the structure of the MDM2-P53 interaction in 1996, SAR405838, NVP-CGM097, MK-8242, RG7112, RG7388, DS-3032b, and AMG232 currently undergo clinical evaluation for cancer therapy. This review is intended to provide a comprehensive and updated overview of MDM2 inhibitors and proteolysis targeting chimera (PROTAC) degraders with a particular focus on how these inhibitors or degraders are identified from starting points, strategies employed, structure-activity relationship (SAR) studies, binding modes or co-crystal structures, biochemical data, mechanistic studies, and preclinical/clinical studies. Moreover, we briefly discuss the challenges of designing MDM2/X inhibitors for cancer therapy such as dual MDM2/X inhibition, acquired resistance and toxicity of P53 activation as well as future directions.